1999
DOI: 10.1038/5030
|View full text |Cite
|
Sign up to set email alerts
|

Primary systemic carnitine deficiency is caused by mutations in a gene encoding sodium ion-dependent carnitine transporter

Abstract: Primary systemic carnitine deficiency (SCD; OMIM 212140) is an autosomal recessive disorder characterized by progressive cardiomyopathy, skeletal myopathy, hypoglycaemia and hyperammonaemia. SCD has also been linked to sudden infant death syndrome. Membrane-physiological studies have suggested a defect of the carnitine transport system in the plasma membrane in SCD patients and in the mouse model, juvenile visceral steatosis. Although the responsible loci have been mapped in both human and mouse, the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
317
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 507 publications
(330 citation statements)
references
References 19 publications
(13 reference statements)
5
317
2
1
Order By: Relevance
“…Several pairs of OCTN2 +/-heterozygous males and females were mated to obtain homozygous OCTN2 -/-mice. Homozygous OCTN2 -/-mice in the litter were genotyped using a RFLP based method; [9] they can also be identified by 4-5 weeks of age when small size and weakness become apparent. Wild type (OCTN2 +/+ ) and homozygous (OCTN2 -/-) pups were sacrificed at 4 weeks of age to identify any GI tract pathology.…”
Section: Animals and Preparation Of Rna And Protein Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pairs of OCTN2 +/-heterozygous males and females were mated to obtain homozygous OCTN2 -/-mice. Homozygous OCTN2 -/-mice in the litter were genotyped using a RFLP based method; [9] they can also be identified by 4-5 weeks of age when small size and weakness become apparent. Wild type (OCTN2 +/+ ) and homozygous (OCTN2 -/-) pups were sacrificed at 4 weeks of age to identify any GI tract pathology.…”
Section: Animals and Preparation Of Rna And Protein Samplesmentioning
confidence: 99%
“…At 3-weeks of age, the body weight of the OCTN2 -/-mice is about 50% compared to that of age-matched wild type mice. Furthermore, OCTN2 -/-mice develop enlarged fatty liver with steatosis of other organs and hypertrophic cardiomyopathy which led to its original designation as the juvenile visceral steatosis (jvs) mouse [9] (Fig-1).…”
Section: Octn2 Null (Octn2 -/-) Mouse Is a Model Of Systemic Carnitinmentioning
confidence: 99%
“…OCTN2 gene is located on chromosome 5q31 with ten exons encoding a 557-amino acid transmembrane protein consisting of 12 transmembrane domains and one ATP-binding domain and predicted molecular mass of 63 kDa (Saito et al 2002;Wu et al 1999). More than 90 mutations have been identified up to date (Amat di San Filippo C et al 2006aFilippo C et al , b, 2008Burwinkel et al 1999;Cederbaum et al 2002;Dobrowolski et al 2005;Koizumi et al 1999;Lamhonwah et al 2002;Li et al 2010;Makhseed et al 2004;Mayatepek et al 2000;Nezu et al 1999;Rahbeeni et al 2002;Spiekerkoetter et al 2003;Tang et al 1999;Vaz et al 1999;Wang et al 1999Wang et al , 2000aWang et al , b, 2001.…”
mentioning
confidence: 99%
“…35 Ganapathy et al 36 demonstrated that many ß-lactam antibiotics that are not recognized by OCTN2 are good substrates for the H + -coupled PEPT1 and PEPT2, and found that cephaloridine, cefoselis, cefepime and cefluprenam significantly inhibited OCTN2-mediated transport of carnitine. These antibiotics possess a quaternary nitrogen, as does carnitine.…”
Section: ) Elimination From the Kidneymentioning
confidence: 99%